2022
DOI: 10.3389/fnbeh.2022.875890
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement History Dependent Effects of Low Dose Ethanol on Reward Motivation in Male and Female Mice

Abstract: Alcohol use disorders (AUDs) are more prevalent in men than in women, though AUD diagnoses in women are growing rapidly, making an understanding of sex differences in alcohol-related behaviors increasingly important. The development of AUDs involves the transition from casual, low levels of alcohol drinking to higher, maladaptive levels. The ability of low dose alcohol to drive reward and drug seeking may differ in males and females, and this could underlie differences in susceptibility to AUD. In this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(32 citation statements)
references
References 54 publications
2
30
0
Order By: Relevance
“…Previously published findings from our lab showed that chronic low‐dose ethanol exposure had no effect on basal reward seeking during training, regardless of reinforcement schedule or sex (Bryant et al., 2022). However, a history of low‐dose ethanol exposure proximal to learning increased reward seeking on a progressive ratio task, and this was associated with alterations in reward magazine checking behavior.…”
Section: Resultsmentioning
confidence: 76%
See 4 more Smart Citations
“…Previously published findings from our lab showed that chronic low‐dose ethanol exposure had no effect on basal reward seeking during training, regardless of reinforcement schedule or sex (Bryant et al., 2022). However, a history of low‐dose ethanol exposure proximal to learning increased reward seeking on a progressive ratio task, and this was associated with alterations in reward magazine checking behavior.…”
Section: Resultsmentioning
confidence: 76%
“…Exposure timing‐dependent effects of ethanol on sucrose reward motivation have been observed under the same training and exposure conditions (Bryant et al., 2022), so this suggests that the effects of ethanol and exposure timing on behavioral strategy selection and motivation may occur via distinct underlying mechanisms. While there were no population level differences observed here, there was a lot of individual variability in sensitivity.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations